China's patent promotion policies and its quality implications. (25th May 2018) - Long, Cheryl Xiaoning; Wang, Jun
Abstract: Based on China's patent data from 1985 to 2010, we find that behind the country's patent number explosion, the overall innovation content of Chinese patents has not achieved proportional growth. An important explanation for this phenomenon is the patent promotion polices ( PPP s), which have prompted the quantitative expansion of patent applications and approvals, but have had negative effects on average patent quality, as proxied by patent application withdrawal rate and patent renewal rate. These patterns are observed both at the provincial level and at the patent level, and they are especially pertinent to patent applications filed by firms, which are the main targets of the PPP s.